Pelatihan Penyusunan Proposal Penelitian Subjek Tunggal (Single Subject Research) bagi Guru-Guru Sekolah Luar Biasa - Heryati, Euis; Tarsidi, Iding; Suherman, Yuyus (Empowerment, 2022)
Research with a single subject is applied and developed in  Special Education because it is relevant to the uniqueness of students with special needs. In addition, there is relevance to the work of special education teachers as educators who cannot be separated from behavior modification activities in two categories, namely: forming, building or maintaining positive behavior and preventing or eliminating negative student behavior. This Community Service activity aims to improve the understanding and skills of SLB teachers in preparing SSR research proposals. The activity was carried out in the form of a workshop or training which was attended by 28 participants.The results of the evaluation showed that this training activity went well and smoothly. The entire series of activities is in accordance with the targets and objectives of the program. The participants were active in discussion activities and question and answer sessions so that they gained better knowledge and skills about SSR research. The results of the evaluation of the tasks assigned to the participants showed that most of the participants had been able to prepare SSR research proposals well.